Family functioning within the context of families with adolescent children in urban India. Issue 1 (30th May 2022) - Hsieh, Hsing‐Fang; Mistry, Ritesh; Kleinsasser, Michael J.; Puntambekar, Namrata; Gupta, Prakash C.; Raghunathan, Trivellore; McCarthy, William; Córdova, David; Maharjan, Gaurab; Desai, Maruti B.; Narake, Sameer; Pednekar, Mangesh S.
Abstract: Research on family functioning within given cultural contexts is needed. This study aims to describe salient dimensions of family functioning in two urban contexts in India and to examine differences in family functioning by sociodemographic groups. We measured differences in family functioning using cross‐sectional survey questionnaire data collected from 13 to 15‐year‐old adolescents and one of their parents/primary caregivers in Mumbai ( n  = 843) and Kolkata ( n  = 913) during 2019–2020. We drew a multi‐stage sample representative of neighborhoods and households in both cities. We assessed a multi‐dimensional family functioning latent factor that included parent‐reported measures (parent–adolescent communication, family cohesion, and parent monitoring of peers) and adolescent‐reported measures (parent support, family cohesion, and parent supervision). Our results support an overall measure of family functioning manifested by multiple dimensions for parent‐ and adolescent‐reported data. Families with male adolescents had worse adolescent‐reported family functioning in Mumbai and parent‐reported family functioning in Kolkata. Higher socioeconomic status was associated with better parent‐reported family functioning in both cities and better adolescent‐reported family functioning in Kolkata. Muslim religious identification in Kolkata and the Hindi native language in both cities were associated with better adolescent‐reported family functioning. Our findings indicate heterogeneity in family functioning across demographic and social‐cultural groups within the two urban contexts of India. This study may inform the development of culturally congruent prevention interventions for families with adolescents in India. 摘要: 对特定文化背景下的家庭功能进行研究是有必要的。本研究旨在描述印度两个城市背景下家庭功能的突出维度，并研究不同社会人口群体的家庭功能差异。我们使用横断面调查问卷数据测量了2019‐2020年期间孟买(n = 843)和加尔各答(n = 913) 13 ‐ 15岁青少年及其父母/主要照顾者的家庭功能差异。我们抽取了一个多阶段的样本，代表了两个城市的社区和家庭。我们评估了多维家庭功能潜在因素，包括父母报告的措施(父母‐青少年沟通、家庭凝聚力和父母对同伴的监督)和青少年报告的措施(父母支持、家庭凝聚力和父母监督)。我们的结果支持对家庭功能的整体衡量，它体现在父母和青少年报告数据的多个方面。在孟买，有男性青少年的家庭的青少年报告的家庭功能较差；在加尔各答，父母报告的家庭功能较差。在两个城市，社会经济地位越高，父母报告的家庭功能越好。在加尔各答，青少年报告的家庭功能较好。加尔各答的穆斯林宗教信仰和印地语母语都与青少年报告的家庭功能较好有关。我们的研究结果表明，在印度的两个城市环境中，不同人口和社会文化群体的家庭功能具有异质性。这项研究可以为印度有青少年的家庭制定文化上一致的预防干预措施提供参考。